2004
DOI: 10.1016/s0738-3991(03)00239-8
|View full text |Cite
|
Sign up to set email alerts
|

Consultation in general practice: a standard operating procedure?

Abstract: The objectives of this study were to describe the features of consultation within general practice with special attention to the differences between short, moderate and long consultations.An analysis of 2801 videotaped consultations of 183 General Practitioners from six countries participating in the Eurocommunication Study was made. The communicative behaviour was gauged by means of the Roter Interaction Analysis System. The consultation can be seen as a "standard operating procedure" consisting of 8% social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
(23 reference statements)
1
23
1
2
Order By: Relevance
“…In our study, the average duration of consultation depended on physician specialization and was greater than the average consultation length observed in Germany (13.0 vs. 7.6 min for GPs), or in the Netherlands, Spain, or the UK, but similar to that observed in Belgian and Swiss GPs [26]. However, unique national features and different healthcare settings must be taken into account, limiting the generalisability of this finding.…”
Section: Discussioncontrasting
confidence: 59%
“…In our study, the average duration of consultation depended on physician specialization and was greater than the average consultation length observed in Germany (13.0 vs. 7.6 min for GPs), or in the Netherlands, Spain, or the UK, but similar to that observed in Belgian and Swiss GPs [26]. However, unique national features and different healthcare settings must be taken into account, limiting the generalisability of this finding.…”
Section: Discussioncontrasting
confidence: 59%
“…Higher quality in terms of less prescriptions of drugs, more health promotion and better outcomes has been found to be positively related to the length of the consultation (Freeman et al 2002;Wilson and Childs 2002). A study on consultation length in six European countries showed that longer visits tended to include more information to the patient and a higher degree of psychosocial talk (Deveugele et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty can be separated into two kinds: behavioral uncertainty and cognitive uncertainty (Berger & Bradac, 1982). The anxiety high-CA patients feel may not come strictly from behavioral uncertainty, as an initial consultation is likely to proceed in a fairly predictable fashion (Deveugele et al, 2004). However, uncertainty is not just about predicting other people's behaviors, but also explaining them; offering the why and the reasons behind their behaviors (Berger & Gudykunst, 1991).…”
Section: Theoretical Rationalementioning
confidence: 99%